Phase I Trial to Assess the Safety, Tolerability, and Preliminary Efficacy of OBI-858 for Treatment of Glabellar Lines - Chih-Hung Lee; Chien-Chih Ou; Tim-Mo Chen (Adis, Springer Healthcare, 2024)
Abstract Introduction OBI-858 is a brand-new botulinum Type A complex toxin with a specific molecular weight of 760 kDa intended for development for both aesthetic and therapeutic applications. This is a phase I, dose-escalation study to evaluate the safety and preliminary efficacy of OBI-858 in subjects with moderate to severe glabellar lines. Methods Each subject received OBI-858 by intramuscular injections with an assigned dose (10 U, 20 U, and 30 U). The safety and preliminary efficacy were evaluated at each of the in-person visits. Results A total of 36 subjects (12 subjects per cohort) were enrolled. The response rates (≥ 1 point) for all groups at maximum frown were assessed at week 4 were 100%. The initial improvement for 30 U occurred at day 3. Response rates revealed benefits lasting 4-6 months or longer. Subject satisfaction at week 4 was high in all groups. Adverse effects were mild and infrequent. Among them, one subject had drug-related AE, and one subject had grade ≥ 3 unrelated AE. Conclusions This study demonstrated that OBI-858 is well tolerated and showed preliminary efficacy. Overall, the OBI-858 has a clinically favorable profile of safety and efficacy that warrants proceeding to the next studies.